2018
DOI: 10.1158/1538-7445.sabcs17-pd3-07
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PD3-07: Safety and efficacy results from a phase 1 study of DS-8201a in patients with HER2 expressing breast cancers

Abstract: Background DS-8201a is a HER2 targeting antibody-drug conjugate (ADC) with high drug to antibody ratio (8:1), a novel linker and topoisomerase I inhibitor as the payload. In preclinical studies, DS-8201a showed efficacy against both trastuzumab emtansine (T-DM1) resistant HER2 positive breast cancer (BC) and against BC with low HER2 expression. The current phase 1 trial is comprised of dose escalation (Part 1) and dose expansion (Part 2) cohorts including patients (pts) with BC, gastric cancer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
5
0
3
Order By: Relevance
“…Bei dem großen Erfolg der Anti-HER2-Therapien auch bei Einsatz nach mehreren Therapielinien wird natürlich weiter nach effektiven Anti-HER2-Therapien gesucht, sodass HER2-positive Patientinnen auch nach einem Progress mit einer wirksamen Anti-HER2-Therapie weiterbehandelt werden können. Ein Beispiel, das bereits in der Vergangenheit vorgestellt worden war, ist das ADC DS-8201a, das Trastuzumab mit einem Topoisomerase-Inhibitor verbindet und gute Wirksamkeit in frühen Therapiestudien zeigte [16][17][18]. Kürzlich wurden nun 2 weitere Anti-HER2-Therapien vorgestellt, Pyrotinib [19] und Margetuximab [20].…”
Section: Paloma-1 [53]unclassified
“…Bei dem großen Erfolg der Anti-HER2-Therapien auch bei Einsatz nach mehreren Therapielinien wird natürlich weiter nach effektiven Anti-HER2-Therapien gesucht, sodass HER2-positive Patientinnen auch nach einem Progress mit einer wirksamen Anti-HER2-Therapie weiterbehandelt werden können. Ein Beispiel, das bereits in der Vergangenheit vorgestellt worden war, ist das ADC DS-8201a, das Trastuzumab mit einem Topoisomerase-Inhibitor verbindet und gute Wirksamkeit in frühen Therapiestudien zeigte [16][17][18]. Kürzlich wurden nun 2 weitere Anti-HER2-Therapien vorgestellt, Pyrotinib [19] und Margetuximab [20].…”
Section: Paloma-1 [53]unclassified
“…DS-8201a is an HER2-targeted antibody-drug conjugate incorporating a humanised HER2 antibody that is attached to a topoisomerase-I inhibitor (deruxtecan) with a high ratio of active substance to antibody of 7 : 8. Data from the phase I study were already presented at the SABCS, revealing a manageable safety profile and promising anti-tumour activity 47 . In the presented study 46 , the response rate in patients with HER2 overexpression was 64.2% and in those with non-overexpression 38.5% 46 .…”
Section: Advanced Breast Cancer – Antibody-drug Conjugatesmentioning
confidence: 99%
“…DS-8201a ist ein HER2-gerichtetes Antikörper-Wirkstoff-Konjugat mit einem humanisierten HER2-Antikörper, der an einen Topoisomerase-I-Inhibitor (Deruxtecan) mit einem hohen Wirkstoff-Antikörper-Verhältnis von 7 zu 8 gebunden ist. Daten der Phase-I-Studie waren bereits beim SABCS präsentiert worden und hatten ein kontrollierbares Sicherheitsprofil sowie eine vielversprechende Antitumoraktivität gezeigt 47 . In der vorgestellten Studie 46 hatten Patientinnen mit einer HER2-Überexpression eine Ansprechrate von 64,2% und solche ohne eine HER2-Überexpression immerhin eine Ansprechrate von 38,5% 46 .…”
Section: Das Fortgeschrittene Mammakarzinom – Antikörper-wirkstoff-kounclassified
“…An advantage is that DX-8951f is not an MDR1 substrate [46, 47]. Four ADCs [Sacituzumab govitecan/IMMU-132 [48], designated as a breakthrough therapy by the FDA; Labetuzumab govitecan/IMMU-130 [49]; DS-8201a [50] and U3-1402 [51]] that employed camptothecin analogues as their payload are being tested in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…The first-in-human anti-CEACAM5 ADC, SAR408701 (payload = DM4), has advanced to phase II trial. In the phase I/II trial of labetuzumab govitecan (payload = SN38), 41 out of 86 patients showed stabilized disease [50, 73]. …”
Section: Introductionmentioning
confidence: 99%